The analysis of fires and rescue operations in Lithuania/Gaisringumo ir gelbėjimo darbų Lietuvoje analizė - Čyras, Petras; Griškevičius, Mečislavas; Jaras, Artūras (Journal of Civil Engineering and Management, 1999)
With the recent increase in the fire and rescue functions the Lithuanian fire fighters have had to endure much higher physical and psychological obligations in fighting for people’s welfare and even life. 11 393 fires with an estimated damage of 21,75 million Litas (LT) occurred in Lithuania in 1997 (Table 1). 227 persons perished in fires, 15 children among them. 134 people were wounded. The majority of them (146) perished in the countryside. 51,81 fire cases fell to 10.000 of the village inhabitants, whereas the average number of fires is 30,71 in Lithuania. In 1997, the number of fire victims was 63 per 1 million of the Lithuanian population, while the analogous rate of the Scandinavian countries is 11–19 persons in average. The maximum number of fires occurred in the year of 1996 (Fig 2). The qualitative and quantitative analysis of fire and rescue services rendered have been recently implemented and suggestions for the improvement of fire registration, reduction of fire rate as well as the increase in rescue services have been provided for. In 1997, the majority of fires broke out in the residential areas, ie blocks of flats and private houses; the number of arson cases increased as well. The basic causes of fire (Fig 3) were negligence in fire precautions (47,76%), improper electrical installations as well as violations of fire regulations (13,0%). 128 persons perished due to negligence. The high level of adults perished in fires is related to the ignorance and negligence in fire safety regulations. The fire brigades have also been committed in carrying out rescue services according to the worldwide experience. In 1997 the Lithuanian rescuers responded to 4095 emergencies (Fig 7). Modern rescue equipment is being used. The rescue team, also, renders urgent medical assistance to the injured on the spot. 205 human lives were saved in 1997 (Fig 8). In 1997, the militarised fire and rescue units liquidated 37 percent of fires, while the non-militarized units extinguished 10% of fires (Fig 9). The average expenses in estimating the complete supply and maintenance of the fire brigade fall to 6.450 LT per one statistical fire. Relative numbers alongside with absolute numbers have been suggested to be used in the fire statistics, these being the rate of the fire frequency, the average fire damage and the relative fire damage rates. These factors characterise the fire rate and enable to determine the fire conditions of an administrative unit or throughout the country, as well as to compare them with other countries. Preventive measures to reduce the fire rate have been presented in the recommendations and conclusions. The Fire Department has been commissioned to undertake all rescue functions in order to further continue the militarisation of the fire brigades, to install automatic smoke detectors in new buildings, to establish lightning conductors in the rural areas and pay particular attention to fixing improper installations. Article in Lithuanian. First Published Online: 26 Jul 2012